Conformational Response to Solvent Interaction and Temperature of a Protein (Histone h3.1) by a Multi-Grained Monte Carlo Simulation - Pandey, Ras B. (Public Library of Science, 2013)
Interaction with the solvent plays a critical role in modulating the structure and dynamics of a protein. Because of the heterogeneity of the interaction strength, it is difficult to identify multi-scale structural response. Using a coarse-grained Monte Carlo approach, we study the structure and dynamics of a protein (H3.1) in effective solvent media. The structural response is examined as a function of the solvent-residue interaction strength (based on hydropathy index) in a range of temperatures (spanning low to high) involving a knowledge-based (Miyazawa-Jernigan(MJ)) residue-residue interaction. The protein relaxes rapidly from an initial random configuration into a quasi-static structure at low temperatures while it continues to diffuse at high temperatures with fluctuating conformation. The radius of gyration (R(g)) of the protein responds non-monotonically to solvent interaction, i.e., on increasing the residue-solvent interaction strength (f(s)), the increase in R(g) (f(s)≤f(sc)) is followed by decay (f(s)≥f(sc)) with a maximum at a characteristic value (f(sc)) of the interaction. Raising the temperature leads to wider spread of the distribution of the radius of gyration with higher magnitude of f(sc). The effect of solvent on the multi-scale (λ: residue to R(g)) structures of the protein is examined by analyzing the structure factor (S( q ),|q| = 2π/λ is the wave vector of wavelength, λ) in detail. Random-coil to globular transition with temperature of unsolvated protein (H3.1) is dramatically altered by the solvent at low temperature while a systematic change in structure and scale is observed on increasing the temperature. The interaction energy profile of the residues is not sufficient to predict its mobility in the solvent. Fine-grain representation of protein with two-node and three-node residue enhances the structural resolution; results of the fine-grained simulations are consistent with the finding described above of the coarse-grained description with one-node residue.